2013
DOI: 10.1111/jpn.12088
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of unpeeled cassava (Manihot esculenta Crantz) root meal supplemented with or without charcoal by broiler chickens

Abstract: A 42-day feeding trial was conducted using 480-day-old, male Marshall broilers to study the utilization of unpeeled cassava root meal (UCRM) supplemented with or without 6 g/kg charcoal. The experimental design was laid out in a 3 × 2 factorial arrangement of treatments having three inclusion levels of UCRM (0, 100 and 200 g/kg) with or without 6 g/kg charcoal supplementation. Each treatment consisted of 80 birds replicated eight times with 10 birds per replicate. Main effect of inclusion level of UCRM and sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…Dry matter, OM, NDF and ADF intakes were optimized at PEG 4000 supplementation levels of 19.62, 19.62, 19.61 and 19.53 g/goat, respectively. This finding is similar to those of Yisehak et al (2013) who reported significant interaction effect of diet and PEG on DM, OM, CP, NDF and ADF. The considerable improvement in the intake of all studied nutrients after the incorporation of PEG reveals the positive impact of PEG when added to tanniniferous diet (Frutos et al 2004).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Dry matter, OM, NDF and ADF intakes were optimized at PEG 4000 supplementation levels of 19.62, 19.62, 19.61 and 19.53 g/goat, respectively. This finding is similar to those of Yisehak et al (2013) who reported significant interaction effect of diet and PEG on DM, OM, CP, NDF and ADF. The considerable improvement in the intake of all studied nutrients after the incorporation of PEG reveals the positive impact of PEG when added to tanniniferous diet (Frutos et al 2004).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Motubatse et al (2008) reported that PEG 4000 supplementation did not affect NDF and ADF digestibility in Pedi goats fed Acacia nilotica leaf meal. Contrary to this result, other authors have reported significant improvement in the apparent digestibility of nutrients (OM and CP) with PEG supplementation (Barry et al 1986; Ben Salem et al 2005; Yisehak et al 2013). The effect of PEG depends on the level of protein in the diet.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…1.10% (carbon); 35.6, 41.9, 42.7, and 48.3%, SEM: 2.72% (nitrogen); and 28.0, 15.0, 27.9, and 27.9%, SEM: 3.31% (phosphorus). This is in accordance with a previous study of Oso et al (2014) who concluded that the inclusion of dietary wood charcoal did not influence the apparent DM and crude protein digestibility of broilers. In the same study, however, the inclusion of charcoal into unpeeled cassava root meals could counterbalance the negative effect of dietary cyanide on the crude protein utilization.…”
Section: Effects Of Dietary Wood Charcoal On Nutrient Accretion and Utilization In Male Broiler Chickenssupporting
confidence: 93%
“…(1983) found that performance of broilers fed 200 g/kg cassava root meal was similar to that of birds fed maize based diets, and Ezeh and Arene (1994) found that cassava root meal could replace up to 75% of dietary maize, resulting in a cost benefit ratio of 1.41:1 against maize. The opposite was however illustrated by Oso et al. (2014) in a study in which unpeeled cassava root meal was fed to broilers up to a level of 200 g/kg.…”
Section: Nutritive Value Of Cassava For Broilersmentioning
confidence: 99%